IMPLEMENTATION OF WASTE REDUCTION POLICIES AND SWEDISH ZERO WASTE MANAGEMENT IN INDONESIA TO REALIZE RESPONSIBLE CONSUMPTION AND PRODUCTION SDGS - Amirulkamar, Said; Safirussalim; Mayzar Mulya, Sayed; Zhukaira, Intan (Penerbit Lafadz Jaya, 2025)
This research aims to analyze the implementation of waste reduction and Swedish zero waste management policies in Indonesia to realize SDGS-responsible consumption and production. This research uses qualitative methods with descriptive analysis, the data sources obtained come from journals, websites, Twitter, and other social media. Data analysis techniques use Nvivo 12 Plus analysis techniques. The research results show several examples of the adoption of zero waste practices from Sweden in Indonesia, namely trash cans, which were inspired by